Social isolation and risk of heart disease and stroke: two large UK prospective studies - Smith, R; Barnes, I; Green, J; Reeves, G; Beral, V; Floud, S (Elsevier, 2021)
Background: Social isolation has been associated with increased risks of coronary heart disease (CHD) and stroke. It is unclear, however, whether the associations differ between fatal and non-fatal events or by the type of isolation (living alone or having few social contacts). We examined these associations in two large UK prospective studies. Methods: Overall 481,946 Million Women Study and 456,612 UK Biobank participants without prior CHD or stroke were followed by electronic-linkage to national hospital and death records. Cox regression yielded adjusted risk ratios (RRs) for first CHD and stroke (separately for deaths without prior hospital admission and for hospital admission as the first event) by three levels of social isolation (based on living alone, contact with family/friends, and group participation). Results: In the two studies combined, there were 42,402 first CHD and 19,999 first stroke events during 7 (SD=2) years follow-up/participant. Social isolation showed little, if any, association with hospital admissions as the first CHD or stroke events. Risks were substantially elevated, however, in the most versus least isolated group if the first event was death without prior hospital admission: RR=1.86 (95% CI 1.63-2.12) for CHD and RR=1.91 (95% CI 1.48-2.46) for stroke. For CHD or stroke death as the first event, RRs were significantly greater (p=0.002) for those living alone versus not (RR=1.60, 95% CI 1.46-1.75) than for those with few versus more social contacts (1.27, 95% CI 1.16-1.38). Results did not differ between studies, or by self-rated health. Conclusion: Social isolation appears to have little direct effect on the risk of developing a first non-fatal CHD or stroke. By contrast, isolation substantially increases the risk that the first such event is fatal, particularly among those living alone, perhaps because of the lack of immediate help in responding to an acute CHD or acute stroke.